Effect of Addition of Sourdough on Physicochemical Characteristics of Wheat and Rice Flour Bread - Jitrakbumrung , Suparat; Therdthai, Nantawan (Agriculture and Natural Resources, 2014)
Gluten-free bread has been developed for people suffering from celiac disease. Nonetheless, the lack of gluten can change the quality of the bread. This study investigated the effect of the addition of sourdough on the physicochemical characteristics of wheat bread and gluten-free bread. In wheat bread, the addition of sourdough (0–15 g per 100 g dough) had no significant effect on the moisture content of the bread. However, the moisture content increased when the sourdough content increased to 22.5–30.0 g per 100 g dough. The addition of sourdough (up to 30 g per 100 g dough) decreased the hardness of the gluten-free bread from 28.94 to 14.95 N. The springiness of the gluten-free bread significantly (P ≤ 0.05) increased from 0.54 to 0.81 with the addition of 22.5–30.0 g per 100g dough sourdough. Likewise, the springiness of the wheat bread significantly increased (P ≤ 0.05) from 0.91 to 0.99. However, with the addition of 30 g sourdough per 100g dough, the hardness of the wheat bread increased significantly (P ≤ 0.05). The cohesiveness of both breads significantly (P ≤ 0.05) increased with an increase in the sourdough content. The addition of sourdough had no significant effect (P > 0.05) on the crust color, but affected the crumb color significantly (P ≤ 0.05). Therefore, the addition of sourdough could change the characteristics of both wheat and gluten-free breads.